2011
DOI: 10.1002/art.30295
|View full text |Cite
|
Sign up to set email alerts
|

Whole stimulated salivary flow: Correlation with the pathology of inflammation and damage in minor salivary gland biopsy specimens from patients with primary Sjögren's syndrome but not patients with sicca

Abstract: Objective. To determine which measure of the salivary flow rate, stimulated or unstimulated, is most strongly associated with pathologic changes in minor salivary gland (MSG) biopsy specimens, and to explore the correlation of salivary flow with oral surface damage, disease duration, and symptom severity in patients with primary Sjögren's syndrome (SS).Methods. In all patients (n ‫؍‬ 32), a biopsy of the MSG was performed, and stimulated salivary flow was assessed. Beginning in 2002, unstimulated salivary flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 26 publications
4
64
2
Order By: Relevance
“…Another limitation is the use of an unstimulated instead of stimulated Saxon test. A report published after the initiation of the present study indicated a better reflection of salivary gland fibrosis with stimulated than with unstimulated flow measurements (Bookman et al 2011). We acknowledge that RTS, as a new ultrasonography technique in rheumatology, is not generally available and that interpretation of ultrasonography and RTS results may be subject to variability in clinical practice.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Another limitation is the use of an unstimulated instead of stimulated Saxon test. A report published after the initiation of the present study indicated a better reflection of salivary gland fibrosis with stimulated than with unstimulated flow measurements (Bookman et al 2011). We acknowledge that RTS, as a new ultrasonography technique in rheumatology, is not generally available and that interpretation of ultrasonography and RTS results may be subject to variability in clinical practice.…”
Section: Discussionmentioning
confidence: 63%
“…Given that fibrotic/ fatty transformation results in functional loss of salivary glands, our findings nevertheless indicate that RTS may be useful in identifying patients with salivary gland atrophy (Bookman et al 2011;Jonsson et al 2011). A proportion of pSS patients may certainly have reduced saliva production because of the inflammation itself, and as the architecture of acini is preserved in these cases, a normal RTS signal can be expected (Bookman et al 2011). The use of salivary gland function as a surrogate for glandular pathology might thus underestimate the true value of RTS in detecting salivary gland atrophy.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Correlations have been made between the extent of the lymphocytic infiltrate (focus score) and salivary gland function; however, to date the contribution of SGEC dysfunction, tissue destruction, autoantibody production, and fibrosis to oral dryness is not clear. An association between fibrosis and saliva production has also been reported 79 and, finally, a potential role for dysregulated neuroendocrine mechanisms has to be taken into consideration. 80 Thus, multiple pathogenic components could contribute to oral dryness and further studies are needed to dissect their relative weight.…”
Section: Tissue Damage/fibrosis and Drynessmentioning
confidence: 99%